Study on migration law of multiscale temporary plugging agent in rough fractures of shale oil reservoirs - Wang, Yang; Fan, Yu; Wang, Xiaojiao (Frontiers in Physics, 2023)
【Abstract】 For unconventional oil and gas reservoirs and deep carbonate reservoirs, temporary plugging fracturing is an important technology to improve oil and gas production. At present, the research of temporary plugging fracturing is mainly focused on the development of high-performance temporary plugging agent, the simulation of fracture growth morphology and the test of plugging ability of temporary plugging agent. There is limited research on the migration law of temporary plugging agents in fractures, which affects the optimization of temporary plugging processes and parameters. Through a crack sealing experimental device, taking into account the influence of rough cracks and crack width, a temporary plugging agent sealing pressure test was conducted. The sealing pressure and the thickness of the dense layer formed by the temporary plugging agent were used to quantitatively characterize the migration law of the temporary plugging agent. This article elucidates the influence of different types, combinations, and concentrations of temporary plugging agents on the sealing pressure. The research resultsshow that the granular temporary plugging agent has better plugging ability than fiber, and it is easier to plug the fractures with small width. Increasing the concentration of temporary plugging agent is beneficial to plugging fractures, and high concentration of temporary plugging agent can achieve higher plugging pressure compared with low concentration of temporary plugging agent.At the same concentration, the plugging pressure of the temporary plugging agent combined with fiber and small particles is lower than that of the temporary plugging agent combined with fiber, small particles and large particles. Increasing the fiber concentration in the composite temporary plugging agent can effectively increase the temporary plugging pressure and shorten the pressure starting time. Compared to smooth fractures, temporary plugging agents are more likely to accumulate and seal in rough fractures. Temporary plugging fracturing technology has been widely used in unconventional fields such as tight gas and shale oil in the Sichuan Basin. The analysis of fracturing injection pressure data shows that fractures will turn several times in the formation after the temporary plugging agent is added to the fracturing fluid, thus increasing the stimulation range.